Combining Surface Templating and Confinement for Controlling Pharmaceutical Crystallization - Manali Banerjee; Blair Brettmann (MDPI AG, 2020)
Poor water solubility is one of the major challenges to the development of oral dosage forms containing active pharmaceutical ingredients (APIs). Polymorphism in APIs leads to crystals with different surface wettabilities and free energies, which can lead to different dissolution properties. Crystal size and habit further contribute to this variability. An important focus in pharmaceutical research has been on controlling the drug form to improve the solubility and thus bioavailability of APIs. In this regard, heterogeneous crystallization on surfaces and crystallization under confinement have become prominent forms of controlling polymorphism and drug crystal size and habits; however there has not been a thorough review into the emerging field of combining these approaches to control crystallization. This tutorial-style review addresses the major advances that have been made in controlling API forms using combined crystallization methods. By designing templates that not only control the surface functionality but also enable confinement of particles within a porous structure, these combined systems have the potential to provide better control over drug polymorph formation and crystal size and habit. This review further provides a perspective on the future of using a combined crystallization approach and suggests that combining surface templating with confinement provides the advantage of both techniques to rationally design systems for API nucleation.